PENGARUH MEDIA FLIPCHART TERHADAP KEMAMPUAN MEMBACA ANAK USIA DINI KELOMPOK B TK NEGERI PEMBINA CIAWIGEBANG - Wahyudin, Erik (Universitas Pendidikan Indonesia (UPI), 2017)
Flipchart is a sheet of an album or calendar that is a bit larger than flipbook, arranged and tied in an order at the top. The paper sheet can be used as a media of teaching and learning, and may be considered as a replacement for the chalkboard or whiteboard. If a sheet is filled up with learning messages, it can be flipped over and the next sheet can be filled with new learningmessages. Flipchart media can only be used for a student group that contains approximately 30 people. This media can be filled with message in the form of letters, drawings, diagrams and figures. Reading for children of kindergarten is basic reading which is one of the aspects of language development that should be developed in kindergarten in her activities such as mentioning vowels and consonants, reading images that have a sentence or a simple word, mentioning objects that have the same sound of the beginning letter, and connecting images with the words. This study aimed to determine (a) the reading ability of early childhood kindergarten Pembina Group B Ciawigebang before the application of flipchart media. (b) the flipchart media application in learning to read in early childhood of Pembina kindergarten Group B Ciawigebang. (c) the flipchart media influence on early childhood reading ability in Pembina kindergarten Group B Ciawigebang. This study used a quantitative approach with the experimental method. The subjects in this study were 24 children in Pembina kindergarten Group B Ciawigebang. Data were collected through observation, testing and documentation. Data were analyzed using t-test. The results of the average post-test are 13 with an increase of 2.2 higher than the average value of the 10.8 pre-test. Based on the results of pre-test and post-test, 12.99 is obtained for tcount value with df = 23, consulted with ttable value at 5% significance level, it is obtained a result of 2.07. These results indicate tcount is greater than the value ttable (12.99 2.07). Ho was rejected and Ha was accepted. It means that flipchart media affected positively on reading ability of early childhood in Pembina kindergarten Group B Ciawigebang.Flipchart adalah lembaran kertas berbentuk album atau kalender yang berukuran agak besar dari flipbook, yang disusun dalam urutan yang diikat pada bagian atasnya. Lembaran kertas tersebut dapat dijadiakan sebagai media pengajaran dan pembelajaran, dan mungkin bisa dianggap sebagai pengganti papan tulis atau white board. Jika lembaran demi lembaran tersebut sudah habis terisi dengan pesan pembelajaran, maka lembaran itu bisa dibalik, kemudian lembar dibaliknya yang masih kosong tersebut bisa diisi dengan pesan pembelajaran. Media ini hanya bisa digunakan untuk kelompok siswa yang berisi sekitar 30 orang. Media flipchart bisa diisi pesan dalam bentuk huruf, gambar, diagram dan angka. Membaca bagi anak Taman Kanak-kanak adalah membaca permulaan yang merupakan salah satu dari aspek perkembangan bahasa yang harus dikembangkan di Taman Kanak-kanak dalam kegiatannnya menyebutkan huruf vokal dan konsonan, membaca gambar yang memiliki kalilmat atau kata sederhana, menyebutkan benda yang memiliki bunyi huruf awal yang sama, dan menghubungkan gambar dengan tulisan. Penelitian ini menggunakan pendekatan kuantitatif dengan metode eksperimen. Subjek dalam penelitian ini adalah anak Kelompok B TK Negeri Pembina Ciawigebang berjumlah 24 anak. Data dikumpulkan melalui observasi, tes dan dokumentasi. Teknik analisis data menggunakan uji t. Hasil penelitian dari rata-rata post-test yaitu 13 dengan peningkatan sebesar 2,2 lebih tinggi dari nilai rata-rata pre-test yaitu 10,8. Berdasarkan hasil pre-test dan post-test diperoleh nilai thitung sebesar 12,99 dengan dk= 23 dikonsultasikan dengan nilai ttabel pada taraf signifikasi 5% diperoleh hasil 2,07. Dari hasil tersebut menunjukkan nilai thitung lebih besar daripada nilai ttabel (12,99 2,07) hasilnya tolak Ho dan Ha diterima artinya media flipchart berpengaruh positif terhadap kemampuan membaca anak usia dini Kelompok B TK Negeri Pembina Ciawigebang.